Multi-threaded QoS Architecture for Multimedia Services over Software Defined Networks (International Journal of Engineering and Computer Science, 2018)
This paper presents novel multi threaded controller-forwarder architecture to support QoS for multimedia streaming over SDN. We foresee that, large network is partitioned into domains; each domain is managed by a controller, where each controller performs optimal QoS routing and shares the routing information with other domain controllers. To this effect, this paper proposes (i) an algorithm for super controller managing inter domain routing, (ii) an algorithm for controller managing intra domain routing, to find out an optimized QoS routes. We apply these extensions to streaming videos and compare the performance of proposed architecture with single threaded controller-forwarder architecture. Our experimental result shows that the proposed architecture performs faster than the single threaded controller-forwarder architecture.